Evaluation of Temperature-Dependent Complex Refractive Indices of Supercooled Liquid Water Using Downwelling Radiance and In-Situ Cloud Measurements at South Pole - Rowe, Penny M; Walden, Von P; Brandt, Richard E; Town, Michael S; Hudson, Stephen R; Neshyba, Steven (Journal of Geophysical Research: Atmospheres, 2022)
Clouds have a large effect on the radiation budget and represent a major source of uncertainty in climate models. Supercooled liquid clouds can exist at temperatures as low as 235 K, and the radiative effect of these clouds depends on the complex refractive index (CRI) of liquid water. Laboratory measurements have demonstrated that the liquid-water CRI is temperature-dependent, but corroboration with field measurements is difficult. Here we present measurements of the downwelling infrared radiance and in-situ measurements of supercooled liquid water in a cloud at temperatures as low as 240 K, made at South Pole Station in 2001. These results demonstrate that including the temperature dependence of the liquid-water CRI is essential for accurate calculations of radiative transfer through supercooled liquid clouds. Furthermore, we show that when cloud properties are retrieved from infrared radiances (using the spectral range 500–1,200 cm−1) spurious ice may be retrieved if the 300 K CRI is used for cold liquid clouds (∼240 K). These results have implications for radiative transfer in climate models as well as for retrievals of cloud properties from infrared radiance spectra.
Keywords: Antarktis; Sydpolen; atmosfæren; geofysikk; klimamodeller

Subglacial Geology and Geomorphology of the Pensacola-Pole Basin, East Antarctica - Paxman, Guy J G; Jamieson, Stewart S R; Ferraccioli, Fausto; Jordan, Tom A; Bentley, Michael J; Ross, Neil; Forsberg, René; Matsuoka, Kenichi; Steinhage, Daniel; Eagles, Graeme; Casal, Tania G (Geochemistry, Geophysics, Geosystems, 2019)
The East Antarctic Ice Sheet (EAIS) is underlain by a series of low-lying subglacial sedimentary basins. The extent, geology, and basal topography of these sedimentary basins are important boundary conditions governing the dynamics of the overlying ice sheet. This is particularly pertinent for basins close to the grounding line wherein the EAIS is grounded below sea level and therefore potentially vulnerable to rapid retreat. Here we analyze newly acquired airborne geophysical data over the Pensacola-Pole Basin (PPB), a previously unexplored sector of the EAIS. Using a combination of gravity and magnetic and ice-penetrating radar data, we present the first detailed subglacial sedimentary basin model for the PPB. Radar data reveal that the PPB is defined by a topographic depression situated ~500 m below sea level. Gravity and magnetic depth-to-source modeling indicate that the southern part of the basin is underlain by a sedimentary succession 2–3 km thick. This is interpreted as an equivalent of the Beacon Supergroup and associated Ferrar dolerites that are exposed along the margin of East Antarctica. However, we find that similar rocks appear to be largely absent from the northern part of the basin, close to the present-day grounding line. In addition, the eastern margin of the basin is characterized by a major geological boundary and a system of overdeepened subglacial troughs. We suggest that these characteristics of the basin may reflect the behavior of past ice sheets and/or exert an influence on the present-day dynamics of the overlying EAIS.
Keywords: Antarktis; Sydpolen; Sørpolen; geofysikk; geomorfologi; glasiologi; innlandsis; subglasial geologi; subglasial topografi

Carsten Borchgrevink and the Southern Cross Expedition, 1898-1900 - Riffenburgh, Beau; Kløver, Geir O (Red.) (The Fram Museum, 2017)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Hiihtovaellus etelänavalle : eräretki Roald Amundsenin jäljissä - Aasheim, Stein P; Paarma, Susanna (Gummerus, 2014)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

Sydpolfarerne Per Savio og Ole Must : liv i grenseland - Sandholm, Unni Aas (Temahefter Aas Sandholm, 2013)
Keywords: Antarktis; Southern Cross; Sydpolen; ekspedisjonen; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

Tryggve Gran : is, luft og krig - Simonsen, Anne Hege (Cappelen Damm, 2013)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; oppdagelsesreiser; polarområdene

I Roald Amundsens skispor : kappløpet til Sørpolen - 100 år etter - Aasheim, Stein P (Cappelen Damm, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

Til Sydpolen - 100 år etter - Johansen, Asle T; Grindhaug, Gaute; Berg, Agnar (Fri flyt, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

Review of Race for the South Pole: the expedition diaries of Scott and Amundsen, by Roland Huntford - Jølle, Harald Dag (Polar Research, 2012)
Roland Huntford is the grand old man among polar historians. After his classic Scott and Amundsen in 1979 (later editions were retitled, The last place on Earth), he wrote a series of books on Norwegian and British polar heroes as well as a thorough study of the history of skiing (2006). Huntford challenged the British admiration of Robert Falcon Scott’s scientific programme and great courage*and insisted that Roald Amundsen’s expedition was far better prepared and carried out. Huntford’s scathing criticism of Scott’s fatal choices and lack of competence dared to assault this cherished British polar icon in a manner that would be unthinkable for Norwegian authors.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; Sørpolen; bokanmeldelser; dagbøker; kappløpet; polarhistorie; polarområdene

Cecilie Skog. Liv Arnesen. Monica Kristensen - Sandberg, Sigri (Polarheltinner : Cecilie Skog, Liv Arnesen, Monica Kristensen, Christiane Ritter, Wanny Woldstad, Ellen Dorthea Nøis, Hanna Resvoll-Holmsen, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjoner; biografier; friluftsliv; kvinner; polarekspedisjoner; polarhistorie

Veivisere under sydkorset - Walsøe, Jan Oskar (Sophie Borchgrevink Nordrum og Ivar O. Nordrum, 2012)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; kartlegging; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Bjaaland, Olav (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Belgica. South Pole. The Heroic Dogs. Darkness and Light. Amundsen and Byrd - Cox, Lynne (South with the sun : Roald Amundsen, his polar explorations, and the quest for discovery, 2011)
Keywords: Antarktis; Roald Amundsen; Sydpolekspedisjonen; Sydpolen; oppdagelsesreiser; polarekspedisjoner; sledehunder

Sydpolsekspedisjonen 1910-1912 - Gjertsen, Hjalmar Fredrik (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Hassel, Sverre (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Johansen, Hjalmar (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Das Eis und der Tod : Scott, Amundsen und das Drama am Südpol - Jostmann, Christian (Beck, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Der Wettlauf zum Südpol : das grösste Abenteuer der Geschichte - Knopp, Guido; Sporn, Mario; Schnier, Marten (Bertelsmann, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Race to the end : Scott, Amundsen and the South Pole - MacPhee, Ross D E (The Natural History Museum, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1914 - Nilsen, Thorvald (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; oseanografi; polarområdene

Le tombeau des glaces : duel mortel pour le pôle - Pierre, Marc (Dorval, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Prestrud, Kristian (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1914 - Schröer, Adolf Hermann; Hansen, Ludvig; Rønne, Martin; Hanssen, Helmer; Kutschin, Aleksandr; Wisting, Oscar; Stubberud, Jørgen; Doxrud, Christian; Stubberud, Jørgen; Hansen, Ludvig; Rønne, Martin (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Antarktis : 71 dager, 1800 kilometer og én million tanker - Skog, Cecilie; Sandberg, Sigri (Gyldendal, 2011)
Keywords: Antarktis; Sydpolen; ekspedisjoner; polarekspedisjoner; reiser; reiseskildringer

Sydpolsekspedisjonen 1910-1912 - Amundsen, Roald (Frammuseet, 2010)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

The South Pole expedition 1910-1912 - Amundsen, Roald (Frammuseet, 2010)
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Roald Amundsens sydpolsferd (1910-1912) = Roald Amundsen's South Pole expedition (1910-1912) - Amundsen, Roald; Diesen, Jan Anders; Lund, Harald Østgaard (Norsk filminstitutt, 2010)
Keywords: Antarktis; Fram (skip); Norge; Sydpolen; Sydpolsekspedisjonen; dokumentarfilmer; ekspedisjonsfilmer; oppdagelsesreiser; polarområdene

Race for the South Pole : the expedition diaries of Scott and Amundsen - Amundsen, Roald; Scott, Robert Falcon; Bjaaland, Olav; Huntford, Roland (Continuum, 2010)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; kjeldeskrift; oppdagelsesreiser; polarområdene; polferder

Antarctic pioneers : the voyage of the Belgica 1879-99 - Kløver, Geir O (Red.) (The Fram Museum, 2010)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; ekspedisjoner; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Belgicaekspedisjonen 1897-1899 : den første overvintring i Antarktis - Amundsen, Roald; Kløver, Geir O. (Red.) (Frammuseet, 2009)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; dagbok; ekspedisjoner; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Vår glemte polarhelt : Carsten Borchgrevink og Southern Cross-ekspedisjonen 1898-1900 - Vogt, David (Aschehoug, 2008)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Nordmenn; Ole Must; Per Savio; Southern Cross; Sydpolen; biografier; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarforskning; polarområdene; samisk

Klimagåten Antarktis - Winther, Jan-Gunnar (Gyldendal, 2008)
Keywords: Antarktis; IPY; Sydpolen; ekspedisjoner; internasjonale polarår; isbreer; klimaendringer; klimatologi; polarforskning

Sydpolen - Skog, Cecilie; Sandberg, Sigri (Cecilie Skog og de tre polene, 2006)
Keywords: Antarktis; Sydpolen; Sørpolen; biografi; ekspedisjoner; reiser; reiseskildringer

The race for the South Pole: Robert Scott and Roald Amundsen (1911-12) - Fleming, Fergus (Off the map : tales of endurance and exploration, 2004)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polareksspedisjoner

Pionerforskning i Sørishavet. Kappløpet mot Sydpolen - Berg, Kåre; Brenna, Åsta (Polarheltene : norske pionerer i Arktis og Antarktis, 2003)
Keywords: Antarktis; Carl Anton Larsen; Carsten Borchgrevink; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner; polarflyving; polarforskning; polarhelter

Pioneering exploration in the Antarctic Ocean. The race for the South Pole - Berg, Kåre; Brenna, Åsta; Aase, Jean (Heroes of the polar wastes : pioneer Norwegian explorers in the Arctic and the Antarctic, 2003)
Keywords: Antarktis; Carl Anton Larsen; Carsten Borchgrevink; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner; polarflyving; polarforskning; polarhelter

The large-scale dynamics of Jutulstraumen drainage basin, East Antarctica - Rolstad, Cecilie Eie (Unipub forlag, 2000)
Keywords: Antarktis; Sydpolen; geografi; glasiologi

Henryk Johan Bull (1893-1895). Carsten E. Borchgrevink (1898-1900). Roald Amundsen (1910-1912) - Rosove, Michael H (Let heroes speak : Antarctic explorers, 1772-1922, 2000)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Henrik Johan Bull; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner

Roald Amundsen's Belgica diary : the first scientific expedition to the Antarctic - Amundsen, Roald; Decleir, Hugo (Red.) (Bluntisham Books, 1999)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; dagbok; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Bernt Balchen : polar aviator - Glines, Carroll V (Smithsonian Institution Press, 1999)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Scott and Amundsen - Honda, Katuiti (The Asahi-Shinbun, 1999)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; polarforskning; polarområdene

Roald Amundsen : en biografi - Bomann-Larsen, Tor (Cappelen, 1998)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolen; biografi; ekspedisjoner; oppdagelsesreiser

I helters spor : Sydpolsekspedisjonens kulturelle organisasjon - Murvold, Hilde Karin (Universitetet i Bergen, 1998)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjoner; ekspedisjoner; etnologi; kultur

Dagboksnotater fra Sydpolen - Hassel, Sverre (Vågemot miniforl., 1997)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Rondespiret - Tollefsen, Ivar; Sand, Vebjørn (Orion forl., 1997)
Keywords: Antarktis; Sydpolen; ekspedisjoner; fjellklatring; klatreekspedisjoner; malerkunst

Dagbok fra Sydpolen - Johansen, Hjalmar (Vågemot forl., 1996)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Snille piker går ikke til Sydpolen - Arnesen, Liv (Damm, 1995)
Keywords: Antarktis; Sydpolen; ekspedisjoner; polarekspedisjoner; reiseskildringer

Cato mot Sydpolen - Hauge, Odd Harald; Bry, Knut; Ebbesen, Lars (Pax, 1995)
Keywords: Antarktis; Nordmenn; Sydpolen; ekspedisjoner; fotokunst; funksjonshemmede; oppdagelsesreiser; polarekspedisjoner; reiser; reiseskildringer

Dronning Maud Land - Tollefsen, Ivar (Mortensen, 1994)
Keywords: Dronning Maud Land; Sydpolen; ekspedisjoner; fjellklatring; polarekspedisjoner

Sydpolen på tvers - Høibakk, Ralph (Gyldendal, 1991)
Keywords: Antarktis; Den Norske Sydpolekspedisjonen 1990; Sydpolen; ekspedisjoner; reiser; reiseskildringer

Sydpolen 1910-1912 - Huntford, Roland; Hoff, Truls (Roald Amundsens oppdagelsesreiser i bilder, 1988)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

The South Pole expedition 1910-1912 - Huntford, Roland (The Amundsen photographs, 1987)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

Scott og Amundsen - Huntford, Roland; Christensen, Jan (Aschehoug, 1980)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Bestemt på å lykkes: Amundsen på Sydpolen - Morris, Edmund (De Fryktløse : oppdagelsesferdene som endret vår verden, 1980)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser

Scott and Amundsen - Huntford, Roland (Hodder & Stoughton, 1979)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; polarforskning; polarområdene

Med Amundsen til Sudpolen. Dagbokblad - Bjaaland, Olav (Syn og segn, 1975)
Keywords: Antarktis; Roald Amundsen; Sydpolen; dagbok; ekspedisjoner; oppdagelsesreiser; polarområdene

Byrd's South Pole Flight - 1929-30 - Isakson, Evelyn Moore (Bernt Balchen, colonel, United states Air force, retired : a special report on the unique career of a great American patriot, 1972)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Kappløpet mot Sydpolen - Jonason, Jan (Tiden, 1971)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Erobringen av Antarktis - Harstad, Herlof (Aschehoug, 1968)
Keywords: Antarktis; Sydpolen; biografier; ekspedisjoner; geografi; historie; oppdagelsesreiser; polarekspedisjoner

Samer i polarforskningen - Nissen, Kristian (Sameliv : Samisk selskaps årbok, 1963)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

The Winning of Australian Antarctica: Mawson's BANZARE voyages, 1929-31, based on the Mawson Papers - Price, Archibald Grenfell (ed.) (Angus and Robertson, 1962)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Kampen om Sydpolen - Gran, Tryggve (Mortensen, 1961)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

U južnogo poljusa god 1900 - Borchgrevink, Carsten Egeberg (1958)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Sydpolen erobring - Richter, Søren (Store norske ekspedisjoner, 1954)
Keywords: Antarktis; Roald Amundsen; Sydpolekspedisjonen; Sydpolen; oppdagelsesreiser

The Conquest of the South Pole - Richter, Søren (Great Norwegian expeditions, 1954)
Keywords: Antarktis; Roald Amundsen; Sydpolekspedisjonen; Sydpolen; oppdagelsesreiser

Antarktis, der snøfokket pisker i juli : om ismassene rundt Sydpolen smelter, stiger verdenshavene med 30 meter : "Norsel"-ekspedisjonen får stor betydning for vitenskapen - [Roer, Nils] (Nå, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; Sydpolen; vitenskap

Hitch your wagon : the story of Bernt Balchen - Knight, Clayton; Durham, Robert C (Bell, 1950)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Boken om Balchen - Knight, Clayton; Durham, Robert C; Halle, R (Steensballe, 1950)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Roald Amundsens opdagelsesreiser - Amundsen, Roald (Gyldendal, 1942)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; geografi; historie; oppdagelsesreiser

Ma derniere expedition aux regions Antarctiques (1936-1937) : avec un aperçu des recherches faites au cours des expéditions entreprises de 1927 à 1937 - Christensen, Lars (Tanum, 1938)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Odd I; Sydpolen; Thorshavn ekspedisjoner; geografi; hvalfangere; hvalfangst

Meine letzte Expedition in die Antarktis 1936-1937 : mit einer Übersicht über die in den Jahren 1927-1937 auf den Fahrten im südlichen Eismeer vorgenommenen Forschungsarbeiten - Christensen, Lars (Tanum, 1938)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Odd I; Sydpolen; Thorshavn ekspedisjoner; geografi; hvalfangere; hvalfangst

Min siste ekspedisjon til Antarktis 1936-1937: med en oversikt over forskningsarbeidene på ferdene 1927-1937 - Christensen, Lars (Tanum, 1938)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Odd I; Sydpolen; Thorshavn ekspedisjoner; geografi; hvalfangere; hvalfangst

My last expedition to the Antarctic 1936-1937 : with a review of the research work done on the voyages in 1927-1937 - Christensen, Lars (Tanum, 1938)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Odd I; Sydpolen; Thorshavn ekspedisjoner; geografi; hvalfangere; hvalfangst

Norvegia rundt sydpollandet : Norvegia-ekspedisjonen 1930-1931 - Isachsen, Gunnar (Gyldendal, 1934)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

The Japanese South Polar Expedition of 1911-1912: A Little-Known Episode in Antarctic Exploration - Hamre, Ivar (The Geographical Journal, 1933)
Keywords: Antarktis; Choku Shirase; Den japanske antarktisekspedisjonen 1910–12; Sydpolen; ekspedisjoner; oppdagelsesreiser

Omkring Löitnant Shirase's Sydpolarexpedition 1910-12 - Hamre, Ivar ([forfatteren], 1932)
Keywords: Antarktis; Choku Shirase; Den japanske antarktisekspedisjonen 1910–12; Sydpolen; ekspedisjoner; oppdagelsesreiser

The South Pole attained: Amundsen in the Fram - Hayes, Gordon J (The conquest of the South Pole : antarctic exploration 1906-1931, 1932)
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolen; ekspedisjoner; oppdagelsesreiser; polarområdene

Antarktiske Forskninger i ældre tid. Sydpolen naas. Flyvningere i Antarktis - Rasmussen, Knud (Polarforskningens saga. Alle tiders store opdagelsesrejser, 1932)
Keywords: Antarktis; Hjalmar Riiser Larsen; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polarekspedisjoner; polarflyving; polarforskning

I. Norske undersøkelser ved Sydpollandet 1929-1931. II. Norvegia-ekspedisjonen 1930-1931 : omseilingen av Sydpollandet - Isachsen, Gunnar (1931)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Med Byrd og Balchen mot Sydpolen : nordmennene i Little America - Petersen, Carl O (Gyldendal, 1931)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; oppdagelsesreiser; polarflyving

Sydpolsforskningens ældre Historie. Det sidste Kapløb mod Sydpolen - Ahlman, Axel; Freuchen, Peter (Kampen om Nord- og Sydpolen, 1928)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polarforskning

Wo das Südlicht flammt : Scotts letzte Südpol-Expedition und was ich dabei erlebte - Gran, Tryggve; Mohr, Adrian (Otto Uhlmann, 1928)
Keywords: Antarktis; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene; reiser

En helt : kaptein Scotts siste færd - Gran, Tryggve (Gyldendal, 1924)
Keywords: Antarktis; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; historie; oppdagelsesreiser; polarområdene; reiser

Amundsen the Opportunist. The Dash for the Pole - Judd, Alfred (The conquest of the poles : and modern adventures in the world of ice, 1923)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polareksspedisjoner

Hvor sydlyset flammer : leir- og ekspeditionsliv paa Antarktis : dagboksoptegnelser fra Scotts ekspedition - Gran, Tryggve (Gyldendal, 1915)
Keywords: Antarktis; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene; reiser

Dagbok: "Den tredje Framfærd. 7de juni 1910 - 6de mars 1912" - Amundsen, Roald (Nasjonalbiblioteket, 1912)
Keywords: Antarktis; Roald Amundsen; Sydpolen; dagbøker; ekspedisjoner; oppdagelsesreiser

"Dagbog tilhørende Fredrik Hjalmar Johansen, ført på 3die Framexpedition, påbegyndt efter afgangen fra Norge, 15de august 1910 til 14de januar 1912" - Johansen, Hjalmar (Nasjonalbiblioteket, 1912)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; oppdagelsesreiser

Sydpol-forskning : en utsigt over dens utvikling gjennem tiderne - Skattum, Ole Jacob (I kommission hos Aschehoug, 1912)
Keywords: Antarktis; Sydpolen; ekspedisjoner; forskning; oppdagelsesreiser

Slædedagboken for turen til Sydpolen - Amundsen, Roald (Utgitt ved Anne Melgård. Nasjonalbiblioteket/bokselskap.no, 1911)
Keywords: Antarktis; Roald Amundsen; Sydpolen; dagbøker; ekspedisjoner; oppdagelsesreiser

Das Festland am Sydpol : die Expedititon zum Sydpolarland in den Jahren 1898-1900 - Borchgrevink, Carsten Egeberg (Schottlaender, 1905)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Nærmest Sydpolen : Aaret 1900 - Borchgrevink, Carsten Egeberg (Gyldendal, 1905)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Südwärts! : die Expedition von 1893-1895 nach dem südlichen Eismeere - Bull, Henrik Johan (Haessel, 1904)
Keywords: Henrik Johan Bull; Sydpolen; Sørishavet; ekspedisjoner; oppdagelsesreiser; polarområdene

Sydover : expeditionen til Sydishavet i 1893-1895 - Bull, Henrik Johan (Aktieforlaget, 1898)
Keywords: Henrik Johan Bull; Sydpolen; Sørishavet; ekspedisjoner; oppdagelsesreiser; polarområdene